Putting Racism on the Table: The Implementation and Evaluation of a Novel Racial Equity and Cultural Competency Training/Consultation Model in New York City. Issue 4 (1st October 2016) - De Jesús, Anthony; Hogan, Jane; Martinez, Robert; Adams, Joan; Hawkins Lacy, Tula
ABSTRACT: This article presents the findings of a mixed-methods study of a racial equity and cultural competency training and case consultation model for child welfare practitioners. Findings suggest that the model enhanced participants' capacity for effective practice with diverse populations. A pretest/posttest instrument and evaluation revealed statistically significant increases of participants' awareness, knowledge, and skills related to culturally diverse populations. In addition, qualitative interview participants described the model as being highly influential and provided evidence of the development of the key skills for culturally effective practice.